Impact of School Nurse Ratios and Health Services on Selected Student Health and Education Outcomes: North Carolina, 2011‐2016. (11th April 2021) - Best, Nakia C.; Nichols, Ann O.; Waller, Anna E.; Zomorodi, Meg; Pierre‐Louis, Bosny; Oppewal, Sonda; Travers, Debbie
Abstract: Background: Determination of adequate school nurse staffing is a complex process. School nurse‐to‐student ratios and the health services school nurses provide to students should be considered. The purpose of this study was to examine the impact of North Carolina school nurse‐to‐student ratios and school nurse health services on the health and education outcomes (eg, absences, grades, self‐management) of students receiving services for asthma and diabetes. Methods: This study of all 115 school districts in North Carolina used the Annual School Health Services Report Survey from 2011 to 2016. Descriptive statistics for health services, programs and outcomes, and generalized linear modeling were used to estimate the association of ratios and health services with asthma and diabetes outcomes. Results: By the 2015‐2016 school year, the average ratio decreased to 1:1086 in North Carolina public schools. Annually, 100, 187 students received services for asthma, 3832 students received services for type 1 diabetes, and 913 students received services for type 2 diabetes. Lower ratios and nurse health services were associated with improved student outcomes, including decreased absences (p = .05), improved grades (p = .05), and student self‐management of their health condition (p = .05). Conclusions: Lower school nurse‐to‐student ratios and services were associated with improvements in students' health and education outcomes.